2019
DOI: 10.1111/jac.12375
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric humidity and genotype are key determinants of the diurnal stomatal conductance pattern

Abstract: Great understanding of the genotypic difference in diurnal stomatal conductance (gs) pattern and the key determinants of the pattern is important for saving water by adopting cultivars appropriately. Fifteen wheat genotypes were studied under different soil conditions and various meteorological conditions with pot cultivation in rain shelter for two years. Genotype and air humidity were found to be key determinants of diurnal gs pattern. All genotypes under low relative humidity (LRH) and most genotypes under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…For example, a single measurement of stomatal conductance at 10:00 h would indicate no stress, due to the transpiration peak, while the multiple continuous measurements revealed that the high transpiration rates at that time of the day are an adaptation to reduced water availability. Hence, the use of only one indicator would have led to misleading conclusions, of difficult interpretation, as pointed out by recent studies [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a single measurement of stomatal conductance at 10:00 h would indicate no stress, due to the transpiration peak, while the multiple continuous measurements revealed that the high transpiration rates at that time of the day are an adaptation to reduced water availability. Hence, the use of only one indicator would have led to misleading conclusions, of difficult interpretation, as pointed out by recent studies [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…All tested genotypes under lower RH (LRH, 15.7%) and most genotypes under higher RH (HRH, 40.7%) displayed a gradual decline pattern from morning through the afternoon. All genotypes presented a single-peak curve pattern under moderate RH (MRH, 28.3%), but the peak time differed among genotypes (Zhang et al, 2019). Based on the previous research, this study aims at (1) clarifying how the influencing factors contribute to the diurnal variation of g s along with transpiration rate (Tr) of wheat under different RH and soil moisture regimes; (2) making clear how P N and Tr of wheat are correlated with g s during the diurnal change under different regimes of soil moisture and RH.…”
Section: Introductionmentioning
confidence: 96%
“…High radiation, temperature and water vapor partial pressure deficit (∆w) may typically induce the so-called midday depression of gas exchange ( [50] and literature cited therein), while particularly additional water deficit [51,52], but also leaf aging, may further eliminate the afternoon peak [53,54] as observed here for the hemp plants. The increase in ∆w could also directly affect leaf conductance, not necessarily mediated through changes in leaf water potential [50,55].…”
Section: Diurnal Gas Exchange Of 'Santhica 27' Plantsmentioning
confidence: 99%